Mediation model of organizational citizenship behavior to improve employee performance with training and emotional intelligence - Darmawan, Dadan; Triatmanto, Boge; Natsir, Mokhamad; Haryadi, Didit; Supriadi, Bambang (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine and analyze factors that can improve employee performance by designing a model formulated by the researcher, including variables such as training and emotional intelligence through organizational citizenship behavior, which can accelerate improvements in employee performance. The research design used by the researcher in this study is a quantitative approach with a causal design. The population in this study consisted of civil servants in the Regional Apparatus Organization in four government agencies in Tangerang Regency, namely the Housing, Settlement and Cemetery Agency, the Spatial Planning and Building Agency, the Road and Water Resources Agency, and the Environment and Sanitation Agency, with a total of 386 respondents comprising groups one to four. The sample in this study consisted of 196 civil servants using a simple random sampling technique. The data analysis technique in this study used IBM SPSS Version 30 and SEM Amos Version 30. The data collection method in this study used a questionnaire with a Likert scale of 1 (strongly disagree) to 5 (strongly agree). The results of this study indicate that training and emotional intelligence significantly influence employee performance, and training and emotional intelligence significantly influence organizational citizenship behavior. Thus, organizational citizenship behavior mediates the influence of training and emotional intelligence on employee performance.